Unlocking therapeutic potential: identifying small molecule inhibitors for SARSCOV-2 variants’ main protease (MPRO) through molecular docking analysis - Chong, Yie Woon; Nurul Izza Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Even with existing emergency drugs, the development of safer and more effective drugs for the treatment of COVID-19 still needs to continue. Virtual screening through a molecular docking approach is a powerful way to discover potential compounds for new drug discovery. In this study, we targeted SARS-CoV-2 wild-type major protease (MPro), beta, lambda and omicron variants, to conduct a virtual screening with a selection of 100 ligands from the PubChem database using AutoDock Vina software. Among the inhibitors that have been identified are ten compounds consisting of ergotamine, 2,5-Dibenzyloxy-3-hydroxyligand-hexanedioic acid bis-[(2-hydroxy-indan-1-YL)-amide], remetinostat, benzamidine, argifin, irinotecan, dihydroergotamine, telmisartan, bromocriptine, and cilengitide, which exhibited the highest binding affinity. Interaction analysis through BIOVIA Discovery Studio showed the binding and interaction modes between these inhibitors and MPro residues of the variant. This mainly refers to 2,5-Dibenzyloxy-3-hydroxyligandhexanedioic acid bis-[(2-hydroxy-indan-1-YL)-amide] and remetinostat which consistently exhibit strong interactions with MPro variants. This research provides promising leads for the development of potential COVID-19 therapeutics. In summary, targeting conserved MPro with small molecule inhibitors provides a solid foundation for combating SARSCoV-2 and its variants, holding promise for effective COVID-19 mitigation.